Wealthtech : wealth and asset management in the fintech age - Schueffel, Patrick (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The book "WealthTech : Wealth and Asset Management in the Fintech Age" is the primary resource for the wealth and asset management technology revolution. It examines the rise of financial technology and its growing impact on the wealth and asset management industry. Written by thought leaders in the global WealthTech space, this volume offers an analysis of the current tectonic shifts happening in wealth and asset management and aggregates diverse industry expertise into a single informative book. It provides practitioners such as wealth managers, bankers and investors with the answers they need to capitalize on this lucrative market. As a primer on WealthTech it offers academics clear insight into the repercussions of profoundly changing business models. It furthermore highlights the concept of the ongoing democratization of wealth management towards a more efficient and client-centric advisory process, free of entry hurdles. This book aggregates facts, expertise, insights and acumen from industry experts to provide answers on various questions including: Who are the key players in WealthTech? What is fueling its exponential growth? What are the key technologies behind WealthTech? How do regulators respond? What are the risks? What is the reaction of incumbent players? This book not only seeks to answer these questions but also touches on a series of related topics: - Get up to speed on the latest industry developments - Understand the driving forces behind the rise of WealthTech - Realize the depth and breadth of WealthTech - Discover how investors react to the growth in WealthTech - Learn how regulators influence the evolution of WealthTech business models - Examine the market dynamics of the WealthTech revolution - Grasp the industry's potential and its effects on connected sectors - Build acumen on investment and entrepreneurial opportunities"-- Provided by publisher.
Keywords: Financial services industry -- Technological innovations.; Asset management accounts.; Fintech.; Business & Economics -- Finance -- General.; Financial technology (fintech); Finance and the finance industry.; elektronické knihy; electronic books